Portrait of Character Education Values in Literary Works Case Study of the Novel Savana by Ima Lawaru - Alim, Juflyn; Suruambo, Juharmin; Rudiyasa, Muh. Yasmin; Lariyos, Zidan; Warda, Syah Atul (Universitas Pahlawan Tuanku Tambusai, 2025)
The study of language and literature entitled Character Education Values in the Novel Savannah by Ima Lawaru explores the character education values presented in the story of a coastal child from Torina who dreams of conquering the world but loses that ambition after becoming a victim of sexual violence by an unknown person. This research aims to describe the character education values and analyze the storyline in the novel. Using a descriptive qualitative method and library research approach, data analysis was carried out through comparison, categorization, and inference techniques. The findings reveal that the novel contains 12 character’s education values: religious values, tolerance, discipline, hard work, creativity, curiosity, national spirit, love for the homeland, respect for achievement, friendship and communication, social concern, and perseverance. These values offer meaningful implications that can be applied in character education in both schools and higher education institutions in Indonesia.